Synthesis of Imidazo[1,2-f]phenanthridines through Palladium-Catalyzed Intramolecular C–C Bond Formation - Saini, Hitesh Kumar; Dhiman, Shiv; Pericherla, Kasiviswanadharaju; Kumar, Anil (Synthesis, 2015)
A simple and convenient approach is developed for the synthesis of the imidazo[1,2-f]phenanthridine framework via post-functionalization of imidazoles obtained through four-component reactions of 1,2-dicarbonyl compounds, anilines, aldehydes and ammonium acetate. The methodology involves palladium-catalyzed direct arylation through sp2 C–H activation. The reported procedure delivers good to high yields of imidazo[1,2-f]phenanthridine derivatives (58–94%) starting from readily available precursors.
Keywords: C–H activation; C–C bond formation; direct arylation; palladium catalysis; imidazo[1,2-f]phenanthridines